2021
DOI: 10.1139/cjpp-2020-0662
|View full text |Cite
|
Sign up to set email alerts
|

Alamandine via MrgD receptor attenuates pulmonary fibrosis via NOX4 and autophagy pathway

Abstract: Alamandine (ALA) and its receptor MrgD were recently identified as components of the renin-angiotensin system (RAS), which confer protection against cardio-fibrosis and renal-fibrosis. However, the effects of ALA on pulmonary fibrosis are unknown. This study was designed to serve two goals: (1) to evaluate ALA/MrgD axis ability in the prevention of Angiotensin Ⅱ (Ang Ⅱ)-induced pulmonary fibrosis in fibroblasts. (2) to determine the effect of ALA in bleomycin (BLM) treated C57B/6 mice. In vivo experiments reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The main sources of PQ-induced ROS production are PQ metabolism in microsomal enzyme systems and mitochondria and the activation of NOX4 in inflammatory and lung target cells (Pourgholamhossein et al, 2018). Recently, targeting NOX4 seemed to be a promising strategy to alleviate experimental lung fibrosis (Sato et al, 2016;Du et al, 2021;Liu et al, 2021). Our results indicated that reducing oxidant formation and oxidative stress might be mechanisms by which the antiapoptotic effect of STM is mediated.…”
Section: Stm Impacted the Tlr4-nox4 Pathwaymentioning
confidence: 68%
“…The main sources of PQ-induced ROS production are PQ metabolism in microsomal enzyme systems and mitochondria and the activation of NOX4 in inflammatory and lung target cells (Pourgholamhossein et al, 2018). Recently, targeting NOX4 seemed to be a promising strategy to alleviate experimental lung fibrosis (Sato et al, 2016;Du et al, 2021;Liu et al, 2021). Our results indicated that reducing oxidant formation and oxidative stress might be mechanisms by which the antiapoptotic effect of STM is mediated.…”
Section: Stm Impacted the Tlr4-nox4 Pathwaymentioning
confidence: 68%
“…Studies have demonstrated that ALA plasmatic concentrations are decreased in IPF patients [24] and that ALA alleviates BLM-induced mice lung fibrosis and angiotensin II (Ang II)-induced fibroblast activation by binding to the MrgD receptor [16,19]. Other studies found that myocardial, vascular, and liver fibrosis could be inhibited by ALA [17,18,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Alamandine (ALA), a novel member of the reninangiotensin-aldosterone system (RAAS), exerts antiinflammation and anti-fibrosis effects via the ALA/MrgD axis [16,17]. Our previous studies have demonstrated the anti-fibrosis and autophagy-modulating effects of ALA in the lungs and liver [18,19]. However, further studies are needed to investigate whether ALA protects against LF activation by regulating Parkin/LC3-mediated mitophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Ang 1-7 can then be cleaved to another angiotensin peptide, alamandin. Ang 1-7 and alamandin have their own specific receptors, MAS1 and MrgD, which demonstrate effects similar to those of Ang II through the AT2 receptor—anti-inflammatory, antifibrotic and vasodilating [ 61 , 62 ]. Ang 1-7 suppresses the development of oxidative stress in CKD models by inhibiting Nox4 expression [ 63 ] and increasing catalase activity in the kidneys [ 64 ].…”
Section: Hormones and Fibrosismentioning
confidence: 99%